The effect of physical activity, body mass index, and sleep quality on students' physical fitness - Akhyar Padhli Nasution; Wilda Welis; Bafirman Bafirman; Nugroho Susanto (Global Econedu, 2026)
This study aimed to examine the direct and indirect effects of physical activity, body mass index, and sleep quality on students’ physical fitness. This quantitative study used a path analysis design involving 85 students from SMA Pembangunan Laboratory, Padang State University. Physical fitness was measured using the Nusantara Student Fitness Test, physical activity using PAQ-A/GPAQ, body mass index through anthropometric measurement, and sleep quality using the Pittsburgh Sleep Quality Index. Physical activity significantly affected physical fitness (β = 0.352, p < 0.001), and sleep quality also had a significant effect (β = 0.353, p < 0.001). Body mass index showed no significant effect (β = −0.026, p = 0.786). The model explained 30.4% of physical fitness variance. Physical activity and sleep quality are key determinants of students’ physical fitness.